(untitled) (Research, Society and Development, 2020)
The Black Indigenous Lands (BIL) are soil units that have as a striking feature the dark coloration and the presence of ceramic and / or lithic fragments and indigenous artifacts incorporated into the surface horizons matrix. The soil can be degraded by natural or human actions, with agriculture and livestock being the main human activities that cause soil degradation. Thus, the objective of this work was to evaluate the spatial variability of the physical attributes of Indian Black Earth under pasture cultivation in Novo Aripuanã, Amazonas, Brazil. A pasture area was mapped using 80 mx 56 m with a regular spacing of 8 m, 88 points at three depths (0.00-0.05; 0.05-0.10 and 0.10-0.20m) totaling 264 samples. These points were georeferenced with a GPS equipment to build the Digital Elevation Model (DEM). The following physical analyzes were performed: macroporosity, microporosity, total soil porosity, soil penetration resistance, soil density and soil gravimetric moisture. From the data obtained, descriptive and geostatistical analyzes were performed. The geostatistical analysis showed that the attributes present great variability, low degree of correlation and moderate degree of dependence; microporosity was the attribute that presented the largest range (55 m) and consequently a greater variability.